Determination of administered prices of foodgrains in India - Sarma, J. S. (International Food Policy Research Institute, 1988)
Agricultural price policies and allied instruments evolved in India in the context of shortages and excess demand during World War II (India 1975). Procurement and distribution of major foodgrains were begun and statutory maximum prices were set, though not strictly enforced. Assurances were given to farmers that the state would purchase foodgrains at fixed prices if market prices fell precipitously; but till 1954 there was no sharp decline in food prices. Minimum prices were announced for wheat, jowar, rice, and maize in 1954-55 when prices started falling sharply (Chopra 1981). The recommendations of the Foodgrain Prices Committee, also known as the Jha Committee, in 1964 provided the foundation for a sound agricultural price policy and a systematic determination of producer prices of major foodgrains and maximum wholesale and retail prices (India 1965a). However, some believe that agricultural price policy in India was more oriented toward consumers' interests, at least until the mid-seventies.